Development of Load Control Algorithm for PV Microgrid - Mohamad Haireen Bin Fatheli; Nur Izzati Zolkifri; Chin Kim Gan; Musa Bin Yusup Lada (Institute of Advanced Engineering and Science, 2017)
The variability of solar irradiance which is caused by the weather conditions could result in the mismatch between the solar PV generation and the demand particularly in the microgrid context. This may lead to the detrimental effects of over/under voltage or over/under frequency. In this regard, this paper presents the laboratory set-up of a grid-connected PV inverter operates in islanding condition. To achieve this, a load control algorithm is proposed to provide the autonomous real time demand control that follows the PV generation to maintain generation-demand equilibrium requirement. The laboratory results show that the proposed load control algorithm can successfully address the voltage and the frequency violation in islanding condition, regardless of the variation of irradiance and power generated by the PV sources.